The impacts of biofuel targets on land-use change and food supply A global CGE assessment - Timilsina, Govinda R. (The World Bank, 2010)
This study analyzes the long-term impacts of large-scale expansion of biofuels on land-use change, food supply and prices, and the overall economy in various countries or regions using a global computable general equilibrium model, augmented by a land-use module and detailed representation of biofuel sectors. The study finds that an expansion of global biofuel production to meet currently articulated or even higher national targets in various countries for biofuel use would reduce gross domestic product at the global level; however, the gross domestic product impacts are mixed across countries or regions. The expansion of biofuels would cause significant land re-allocation with notable decreases in forest and pasture lands in a few countries. The results also suggest that the expansion of biofuels would cause a reduction in food supply. Although the magnitude of the impact on food supply at the global level is not as large as perceived earlier, it would be significant in developing countries like India and those in Sub-Saharan Africa. Agricultural commodities such as sugar, corn, and oil seeds, which serve as the main biofuel feedstocks, would experience significant increases in their prices in 2020 compared with the prices at baseline due to the expansion of biofuels to meet the existing targets